HUBUNGAN EKSPRESI PD-L1 DAN DENSITAS TILS PADA SUBTIPE KARSINOMA OVARIUM: CORRELATION OF PD-L1 EXPRESSION AND TILS DENSITY IN OVARIAN CARCINOMA SUBTYPES - Kadri, Sayed Muhammad; Mariedina, Causa Trisna; Betty; Laksmi, Lidya Imelda; Lubis, Nadjib Dahlan (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2025)
Background: PD-L1 and tumor-infiltrating lymphocytes (TILs) are essential components of the tumor microenvironment, playing key roles in modulating immune responses against ovarian carcinoma. However, the relationship between these two markers remains underexplored, especially across different histopathological subtypesMethods: A cross-sectional analytical study was conducted on 40 ovarian carcinoma cases using immunohistochemistry. PD-L1 expression and TIL density were evaluated in both intratumoral and stromal compartments. The Somers’ D test was used to analyze the correlation between variables.Results: Most patients were aged 40–50 years and presented with stage I disease. The predominant histopathological subtype was serous carcinoma. Intratumoral and stromal TIL densities were mostly low (77.5% and 72.5%, respectively). Positive intratumoral PD-L1 expression was observed in only 5% of cases, while no stromal PD-L1 expression was detected. No statistically significant correlation was found between PD-L1 expression and TIL density, either overall or by subtype.Conclusion: No significant correlation was observed between PD-L1 expression and TIL density in ovarian carcinoma subtypes. The variability in their expression suggests immune microenvironment heterogeneity, supporting the need for separate evaluation of these biomarkers and individualized approaches to immunotherapy. AbstrakLatar Belakang: PD-L1 dan TILs merupakan komponen utama dalam mikrolingkungan tumor yang berperan penting dalam regulasi respons imun terhadap karsinoma ovarium. Hubungan antara keduanya masih jarang dikaji, khususnya pada berbagai subtipe histopatologi.Tujuan: Menilai hubungan antara ekspresi PD-L1 dan densitas TILs pada beberapa subtipe karsinoma ovarium.Metode: Penelitian cross-sectional analitik pada 40 kasus karsinoma ovarium menggunakan pewarnaan imunohistokimia. Ekspresi PD-L1 dan densitas TILs dianalisis pada area intratumoral dan stromal. Uji korelasi Somers’ D digunakan untuk menilai hubungan antar variabel.Hasil: Mayoritas pasien berusia 40–50 tahun dan berada pada stadium klinis I, dengan subtipe terbanyak adalah serous carcinoma. Densitas TILs intratumoral dan stromal sebagian besar tergolong rendah (77,5% dan 72,5%). Ekspresi PD-L1 intratumoral positif ditemukan pada 5% kasus, sedangkan ekspresi PD-L1 stromal tidak ditemukan. Tidak terdapat hubungan yang bermakna antara ekspresi PD-L1 dan densitas TILs, baik secara keseluruhan maupun berdasarkan subtipe.Kesimpulan:Tidak ditemukan korelasi signifikan antara ekspresi PD-L1 dan densitas TILs pada subtipe karsinoma ovarium. Variasi pola ekspresi antar subtipe mencerminkan heterogenitas imun tumor, sehingga diperlukan evaluasi terpisah PD-L1 dan TILs sebagai biomarker serta pendekatan individualisasi dalam terapi imun.